Crystal structure of lead chloride thiocyanate, PbCl(SCN) - Gacemi A. (Zeitschrift für Kristallographie - New Crystal Structures, 2005)
CClNPbS, orthorhombic, Pnma (no. 62), a = 10.166(1) Å, b = 4.255(1) Å, c = 9.589(1) Å, V = 414.8 Å3, Z = 4, Rgt(F) = 0.023, wRref(F2) = 0.067, T = 293 K.